Bullying/Victimization, school bonding and addictive substances try during adolescence - Koufaki, Irini; Andreou, Eleni (Psychology: the Journal of the Hellenic Psychological Society, 2021)
Research findings have shown associations between smoking and bullying behavior, but they have not yet offered a clear picture concerning students involved in bully/victim incidents and whether they had tried addictive substances. Additionally, it seems that the less students feel connected to their school, the more they try addictive substances and the more they get involved in bullying/victimization. The main aim of the present study was to examine the relationship between bullying/victimization, school bonding during adolescence and whether students had tried substances. The sample consisted of 779 students (426 boys and 353 girls) of middle and high schools who were administered a questionnaire concerning school bullying/victimization (categorization of students in bullies, victims, bully/victims and not involved), four parameters of school bonding, namely commitment, attachment, involvement and faith in school rules, and whether they had tried legal and illegal addictive substances. Results showed that the more the students felt connected to their school, the less they had tried addictive substances. Bullies and bully/victims had tried more substances than victims and students not involved in bully/victim incidents, while they felt less connected to their school in terms of commitment and attachment. There was not any statistically significant relationship between involvement in school activities and bullying/victimization. As far as faith in school rules is concerned, not involved students exhibited the highest scores and bully/victims the lowest. The results of this study confirm previous findings in the field of bullying/victimization and are discussed in terms of their implications for school-based interventions.